Perceived stressors of undergraduate dental students at an Australasian dental school - Garde, Siddharth; Adam, Lee A; Tawse-Smith, Andrew (IIUM Journal of Orofacial and Health Sciences, 2021)
The purpose of this study was to identify the perceived stressors of Bachelor of Dental Surgery (BDS) students at a prominent Australasian dental school using the Dental Environment Stress (DES) questionnaire. All BDS students were emailed a modified version of the DES questionnaire. The questionnaire consisted of forty questions: seven collecting demographic information, one free text question and thirty-two items related to various sources of stress, grouped into four subscales: 1) Academic 2) Clinical and patient related 3) Environmental and 4) Personal. Students were asked to rate the items on a five-point Likert-type scale ranging from not at all stressful (1) to extremely stressful (5). Of the 314 students emailed, 165 responded to the survey (52.5% response rate). The academic subscale had the highest self-reported mean stress score (3.09 ± 0.68 (SD)); compared with the clinical (2.71 ± 0.77), environmental (2.40 ± 0.77) and personal (2.37 ± 0.68) subscales. There was a statistically significant difference (p<0.05) in self-perceived clinic related stress levels between male and female students, with female students reporting more stress. There was also a statistically significant difference in self-perceived environmental stress between second- and third-year students (p=0.037), and in perceived personal stress between students based on their English language status (p=0.034). These findings can enable identification of students who might be at higher risk of stress to ensure support is provided for them; specifically, female students and students in their third year. Results also indicate the need to develop interventions to help all students with academic stressors.